National Unity and Integration: From the Youth Pledge to the Present Day - Subaida, Sitti; Putri, Fia Alifah; Iskandar, Wahyu (Yayasan Zia Salsabila, 2024)
This study aims to explore the impact of inquiry-based learning strategies on improving the citizenship literacy of elementary school students through the teaching of the Youth Pledge history. The research problem addressed in this study is how inquiry-based learning methods can influence students' understanding of national unity, patriotism, and national identity values. This research uses a qualitative approach with a case study design involving students, teachers, and school principals from several elementary schools in Kendari City. Data collection techniques included interviews, observations, and documentation, which were then analyzed using N-Vivo software to identify emerging themes from the data. The findings show that the implementation of inquiry-based learning significantly enhanced students' understanding of national values and increased their engagement in the learning process. Students also demonstrated improved citizenship literacy, including critical thinking and social responsibility. The implications of this study suggest that inquiry-based learning methods can be an effective approach to strengthening citizenship character and national understanding in elementary schools. This study makes a significant contribution to the development of more interactive and reflective history teaching methods in Indonesia.